Phonological Simplification in K-Pop English Lyrics: Connected Speech in Aespa's Title Tracks - Mentari Antika Putri; Anggi Rizky Firdhani; Listya Arum Ridhawati; Faza Hannan Purinanda (Jurnal Bahasa Inggris Terapan, 2026)
The growing presence of English in K-pop lyrics has drawn attention to how Korean singers produce English in professional recording contexts. This study analyzes phonological simplification in the English lyrics of Aespa's title tracks, focusing on the types and frequencies of connected speech processes present in their recordings. Using a qualitative descriptive approach, the data consist of five title tracks released between 2023 and 2025: Spicy, Supernova, Armageddon, Whiplash, and Dirty Work. Audio recordings were transcribed using narrow IPA transcription and compared against General American citation forms, with each phonological difference coded as a connected speech process based on predefined categories from connected speech theory. The analysis identified 77 tokens across six process types. Reduction (45.5%) and elision (27.3%) are the most frequent, while substitution (14.3%), lenition (6.5%), assimilation (5.2%), and linking (1.3%) occur less frequently but appear consistently across all five songs. These findings show that phonological simplification in Aespa's English singing is systematic rather than random, shaped by both the natural tendencies of English connected speech and the influence of Korean phonological patterns. This study contributes an empirical account of how English is phonologically adapted within a K-pop performance context.